Familiar Travelogues of Some Unfamiliar Travelers - Sobia Manzoor (بازیافت)
<span style="font-size: 14.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Travelogue is a historic document wherein the writer describes the experiences and observations of his journey. In fact, the journey of man started since the time immemorial, but the trend of travelogue writing started in the era of Chander Gupt Moriya (3 BC). “Ajaibaat-a-Farang” of Yousaf Khan Kambal Posh is the first recognized travelogue ever written in Urdu. Afterwards, many other writers took this genre to its intellectual and technical perfection.  This document  present the study on foreigners travelogue writings related to Pakistan describing their observations, experiences and rich feelings about Pakistan, its land and people. In these selected travelogues, translated into Urdu , study will high light the positive influence of Pakistan, its people and land on the travelers through their writings.